Application of a sedation scoring system in dogs following premedication : thesis is submitted by Deepti Deshpande to fulfil the requirements for the degree of Masters of Veterinary Studies in the Institute of Veterinary, Animal and Biomedical Sciences, College of Sciences, Massey University, Palmerston North, New Zealand - Deshpande, Deepti (Massey University, 2014)
Pharmacogenetics is the study of how variations in the genome influence drug pharmacokinetics (the body's effect on the drug) and pharmacodynamics (the drug's effect on the body). The MDR1 gene codes for a membrane-bound drug transporter protein, P-glycoprotein (P-gp) that transports drugs across the cell membrane using an energy-dependent mechanism. Anecdotal reports in the literature suggested that dogs with a mutation in the MDR1 gene (MDR1-1Δ) show increased sensitivity to routinely used veterinary sedatives such as acepromazine and butorphanol, resulting in increased duration and depth of sedation. This study has 3 aims. First is to gain experience with a sedation scoring system that can be used to assess the level of sedation. The second aim is to assess the difference in sedation of dogs premedicated with dexmetomidine and acepromazine. The third aim is to investigate the effect of acepromazine (n=29) and a combination of acepromazine and butorphanol (n=12) on MDR1 genotyped rough-coated collies. In the study assessing the sedation of dogs premedicated with dexmadetomidine and acepromazine, 30 dogs scheduled for orchidectomy were divided into two groups; the DEX group (n=15) and the ACE group (n=15). Dogs in the DEX group received dexmedetomidine (125 μg/m2) and morphine (0.5 mg/kg) while the dogs in the ACE group received acepromazine (0.04 mg/kg) and morphine (0.5 mg/kg). The dogs were sedation scored at 0, 10, 20 and 30 minute intervals. The dogs in the DEX group had a statistically higher sedation score at 30 minutes than the dogs in the ACE group (p value =0.0189). Dogs premedicated with dexmedetomidine had a higher sedation score than dog’s premedicated acepromazine at 30 minutes. The heart rate, respiratory rate and mean arterial blood pressure were not different between the DEX and the ACE group at 30 minutes post administration of premedication agent. The second study investigated the effects of acepromazine and a combination of acepromazine and butorphanol in dogs carrying the MDR1-1Δ mutation. Genotyping for the MDR1-1Δ mutation was performed in 31 rough-coated collies. Dogs were considered healthy based on clinical history, physical examination, complete blood count, serum chemistry and urinalysis. Twenty-nine of the 31 rough coated collies were deemed healthy and were enrolled in the sedation trial assessing the effects of acepromazine on the MDR1-1Δ mutants. A subset of the 29 rough coated collies was enrolled in the study assessing the effects of combination of acepromazine and butorphanol. The rough coated collies were divided in 3 groups based on their genotype: homozygous mutants, heterozygous carriers and normal group. After administration of acepromazine (0.04 mg/kg, IV) or a combination of acepromazine (0.04 mg/kg) and butorphanol (0.05 mg/kg), sedation scoring was performed at 0, 30 minutes, 60 minutes, 90 minutes, 2 , 2.5 , 3 , 4 and 6 hour intervals by an observer blinded to the results of the MDR1 genotype. Following administration of acepromazine, homozygous mutant collies (MDR1 -/-) (n = 10) reached a greater level of sedation and remained sedated for a longer duration as compared to the heterozygous carriers (MDR1 +/-) (n =10) and wild-type collies (MDR1 +/+) (n = 9) (p= 0.0176). A subset of 12 dogs was sedated with a combination of acepromazine (0.04 mg/kg) and butorphanol (0.05 mg/kg). Heterozygous carriers (MDR1 -/+) had significantly higher sedation scores than homozygous mutants (MDR1 -/-) and normal groups (MDR1 +/+) when sedated with the combination (p=0.0423). This unexpected result may have been due to the small number of dogs tested. The author recommends lower dosing of acepromazine and butorphanol in dogs that are homozygous mutants to the MDR1-1Δ mutation and recommends the constant monitoring of sedation.
Keywords: Pharmacogenetics; Pharmacokinetics; Pharmacodynaics; Sedation in dogs; Veterinary sedatives; Dexmetomidine; Acepromazine